Dengansin(a+b) = sin(a)cos(b) + sin(b)cos(a)sin(a-b) = sin(a)cos(b) - sin(b)cos(a)cos(a+b) = cos(a)cos(b) - sin(a)sin(b)cos(a-b) = cos(a)cos(b) + sin(a)sin(b)maka hasil darisin 15°(cos 105° – sin 75°) =sin (45°-30°)(cos(45°+60°) – sin(45°+30°)) =(sin45cos30-sin30cos45)(cos45cos60-sin45sin60 - (sin45cos30+sin30cos45)) =(½√2(½√3)-½(½√2))(½√2(½)-½√2(½√3)-[½√2(½√3)+½(½√2)]) =(¼√6 - ¼√2)(¼√2-¼√6 - (¼√6+¼√2)) =(¼√6 - ¼√2)(¼√2-¼√6 - ¼√6-¼√2) =(¼√6 - ¼√2)(- ½√6) =-⅛(6) + ⅛√12 =-¾ + ⅛√4√3 =-¾ + ⅛(2√3) =¼√3 - ¾ =
semogq bermanfaat........
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
Dengan
![\bf\frac{1}{4}(\sqrt{3}-3) \bf\frac{1}{4}(\sqrt{3}-3)](https://tex.z-dn.net/?f=%5Cbf%5Cfrac%7B1%7D%7B4%7D%28%5Csqrt%7B3%7D-3%29)
sin(a+b) = sin(a)cos(b) + sin(b)cos(a)
sin(a-b) = sin(a)cos(b) - sin(b)cos(a)
cos(a+b) = cos(a)cos(b) - sin(a)sin(b)
cos(a-b) = cos(a)cos(b) + sin(a)sin(b)
maka hasil dari
sin 15°(cos 105° – sin 75°) =
sin (45°-30°)(cos(45°+60°) – sin(45°+30°)) =
(sin45cos30-sin30cos45)(cos45cos60-sin45sin60 - (sin45cos30+sin30cos45)) =
(½√2(½√3)-½(½√2))(½√2(½)-½√2(½√3)-[½√2(½√3)+½(½√2)]) =
(¼√6 - ¼√2)(¼√2-¼√6 - (¼√6+¼√2)) =
(¼√6 - ¼√2)(¼√2-¼√6 - ¼√6-¼√2) =
(¼√6 - ¼√2)(- ½√6) =
-⅛(6) + ⅛√12 =
-¾ + ⅛√4√3 =
-¾ + ⅛(2√3) =
¼√3 - ¾ =
semogq bermanfaat........